Preparation and characterization of licorice-chitosan coatings for postharvest treatment of fresh strawberries - Quintana, Somaris E.; Llalla, Olimpia; García Zapateiro, Luis A.; García Risco, Mónica R.; Fornari, Tiziana (MDPI, 2023)
Several plant extracts are being investigated to produce edible coatings, mainly due to their antioxidant and antimicrobial activities. In this study, licorice root extracts were produced by ultrasound-assisted extraction and were combined with chitosan to elaborate edible coatings. Different solvents and temperatures were used in the extraction process, and the antioxidant and antimicrobial activity of the extracts were assessed. The most bioactive extracts were selected for the development of the edible coatings. The rheological properties of the coatings were studied, and they were applied on strawberry to evaluate their physicochemical and microbiological properties. The addition of licorice extract to chitosan resulted in positive effects on the rheological properties of the coatings: the incorporation of phytochemicals to chitosan decreased the shear stress and improved the restructuring ability of the coating solutions. The films presented a reduction of the Burger model parameter, indicating a reduction of rigidity. Furthermore, the strawberry coated with chitosan and licorice extract maintained good quality parameters during storage and showed the best microbiological preservation in comparison with controls. Hence, the use of chitosan with licorice extract is a potential strategy to produce edible coating for improving the postharvest quality of fruits.